2008
DOI: 10.1160/th07-08-0509
|View full text |Cite
|
Sign up to set email alerts
|

The prostacyclin analogue iloprost increases circulating endothelial progenitor cells in patients with critical limb ischemia

Abstract: Patients with critical limb ischemia (CLI) have low levels of endothelial progenitor cells (EPC). Iloprost has been demonstrated to stimulate vascular endothelial growth factor (VEGF) and promote angiogenesis. We investigated the effects of iloprost on EPC levels in vivo in CLI patients. Twenty-three patients with stage III and IV CLI were treated with iloprost for four weeks, improving clinical and instrumental parameters. Mononuclear cells isolated from peripheral blood were cultured to obtain "early" EPC, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…In addition to the normal vascular supply promotion of the angiogenesis to the ischemic wound healing is necessary and can be observed by the levels of the VEGF in the molecular level. Di Stefano et al 6 reported that iloprost increased the levels of VEGF and promoted the angiogenesis in vivo so that the progenitor endothelial cell number expanded and ischemic limbs showed clinical improvement. We found that early administration of iloprost enhanced VEGF production in the tissue and there was a statistically significant increase compared to the control group (group 1 with iloprost therapy after ischemia vs. group 2 without iloprost therapy) (p=0.002) but there was no difference after 72 hours (p=0.6) Histopathologically increased levels of vascularization was observed in group 1 at 24 th hour that and although the increase was sustained even at 72 hours it was not statistically significant.…”
Section: Histopathological Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the normal vascular supply promotion of the angiogenesis to the ischemic wound healing is necessary and can be observed by the levels of the VEGF in the molecular level. Di Stefano et al 6 reported that iloprost increased the levels of VEGF and promoted the angiogenesis in vivo so that the progenitor endothelial cell number expanded and ischemic limbs showed clinical improvement. We found that early administration of iloprost enhanced VEGF production in the tissue and there was a statistically significant increase compared to the control group (group 1 with iloprost therapy after ischemia vs. group 2 without iloprost therapy) (p=0.002) but there was no difference after 72 hours (p=0.6) Histopathologically increased levels of vascularization was observed in group 1 at 24 th hour that and although the increase was sustained even at 72 hours it was not statistically significant.…”
Section: Histopathological Resultsmentioning
confidence: 99%
“…Iloprost was also reported to have liver and kidney sparing properties in ischemia-reperfusion damage 4,5 . In patients with critical limb ischemia iloprost increased the endothelial progenitor cells in vivo and induced angiogenesis 6 . Iloprost was also reported by Lehman et al 7 that it has a protective effect against endotoxin induced intestinal damage in rats and that was attributed to the decrease in leucocyte adhesion in the circulation and decrease in oxitadive damage by inhibition of proinflammatory cytokines such as TNFalpha and IL-6 8,9 .…”
Section: Introductionmentioning
confidence: 97%
“…Other medications, such as iloprost (prostacyclin, PGI2), cilostazol (phosphodiesterase-3 inhibitor) and others are widely used in CLI patients to relieve symptoms and signs of ischemia. Because iloprost increases the endothelial progenitor cell number in peripheral blood in vivo, it may have a direct effect on therapeutic angiogenesis (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…The use of a biomarker, such as EPC, may be attractive and may help to identify RA patients at high risk for coronary artery disease, allowing for a more aggressive risk-reducing strategy. Equally exciting might be the promise of possibly manipulating EPC through stem cell treatment, perhaps reducing atherosclerotic burden in patients most at risk 22 . Further work in this area is clearly needed.…”
Section: Rheumatologymentioning
confidence: 99%